A PADRONIZAÇÃO DE PROCEDIMENTOS COMO ESTRATÉGIA DE SISTEMATIZAÇÃO DO CONHECIMENTO: O CASO DA IMPLANTAÇÃO DO MANUAL DE SEGURANÇA EM UMA EMPRESA DE ENERGIA. - Bezerra, Marcela de Sá Marques (2011)
Working with knowledge in an integrated way within company s processes indicates the knowledge management as a systematic of work in the organizational environment, in order to reach the objectives of an organization. In this context, standardization process through procedures development has great importance, because they are the implicit experience of the company and they work as a successful solution for complex tasks, contributing for the effectiveness and efficiency of the processes. Talking about Safety, high numbers of accidents have been currently still observed and it can be noted that the majority of them occurs due to lack of adequate and standardized safety processes, that is, the greatest cause of the faults are not the details of things that were wrong, but really the lack of adequate procedures, methodologies and standards. Regarding this scene, the objective of this study is to discuss the influence of the procedures standardization as strategy of knowledge systematization, through an assessment of the process of generation, retention, dissemination and application of the knowledge, using the case study of the Safety Manual in the upstream department of a Brazilian energy company. As an option of methodology, it is proposed a research which is classified as exploratory, bibliographical, qualitative and applied, supported for a bibliometric research. This study is also complemented by a survey research. As result, the main subjects in knowledge management are presented, through the identification of the implementation process for knowledge management and the discussion of the influence of standardization as a strategy of knowledge systematization.